Effects of Rivastigmine and Donepezil on Brain Acetylcholine Levels in Acetylcholinesterase-Deficient Mice - Runa S. Naik; Joachim Hartmann; Cornelia Kiewert; Ellen G. Duysen; Oksana Lockridge; Jochen Klein (Frontiers Media S.A., 2009)
Purpose. Alzheimer´s disease is characterized by a dysfunction of central cholinergic systems and is treated by inhibitors of acetylcholinesterase (AChE). This study tests the effect of two AChE inhibitors in therapeutic use, rivastigmine and donepezil, in mice that are devoid of AChE (AChE-/- mice). Rivastigmine is an inhibitor of both AChE and butyrylcholinesterase (BChE) whereas donepezil is a selective inhibitor of AChE. Methods. We have used in vivo microdialysis to investigate the effects of the two drugs on the extracellular concentration of acetylcholine (ACh) in the hippocampus of AChE-/- mice. Results. Extracellular ACh levels in the hippocampus were 30-fold elevated in AChE-/- mice compared to wild-type (AChE+/+) animals. Infusion of rivastigmine (1 and 10 µM) caused a further doubling of ACh levels in AChE-/- mice within 90-120 min. In contrast, infusion of donepezil (1 µM) did not affect hippocampal ACh levels in AChE-/- mice although it increased ACh levels more than twofold in wild-type mice. Conclusions. In the absence of AChE, rivastigmine enhances the levels of extracellular ACh by inhibiting BChE. This finding may be of therapeutic relevance because BChE activity is preserved, but AChE activity is strongly decreased, in late-stage Alzheimer´s disease.